Learners' stories : difference and diversity in language learning - Benson, Phil.; Nunan, David (Cambridge : New York : Cambridge University Press, 2005)
"This book focuses on learners as people, and the ways in which language learning is embedded within the personal and social lives of learners. It shows how first-person accounts of language learning can be used practically both inside and outside the classroom."--Jacket.
Includes bibliographical references (p. 157-172) and index.
Keywords: Language and languages -- Study and teaching; Fremdsprachenlernen; Individualität